2021
DOI: 10.1111/cyt.13085
|View full text |Cite
|
Sign up to set email alerts
|

The role of the IAC Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy and the ACR Breast Imaging‐Reporting and Data System in the evaluation of breast lesions

Abstract: Background Stratification of breast lesions for appropriate management is achieved through an integration of clinical examination, imaging, and fine needle aspiration biopsy (FNAB). The current study aimed to evaluate the combined effectiveness of the widely used Breast Imaging‐Reporting and Data System (BI‐RADS) with the recently proposed International Academy of Cytology (IAC) Yokohama System for Reporting Breast Fine Needle Aspiration Biopsy Cytopathology. Methods A retrospective analysis was done on all br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These studies report ROM in the different categories of IACYS. The ROM was ranged in categories II 0.4% to 8.3%, III 1.3% to 50%, IV 55.55% to 100%, and V 97% to 100% 4–18 . The ROM in category I without ROSE ranges from 0% to 60.87% 4–18 and 0% to 11.11% 8,17 with ROSE.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These studies report ROM in the different categories of IACYS. The ROM was ranged in categories II 0.4% to 8.3%, III 1.3% to 50%, IV 55.55% to 100%, and V 97% to 100% 4–18 . The ROM in category I without ROSE ranges from 0% to 60.87% 4–18 and 0% to 11.11% 8,17 with ROSE.…”
Section: Discussionmentioning
confidence: 96%
“…The ROM was ranged in categories II 0.4% to 8.3%, III 1.3% to 50%, IV 55.55% to 100%, and V 97% to 100% 4–18 . The ROM in category I without ROSE ranges from 0% to 60.87% 4–18 and 0% to 11.11% 8,17 with ROSE. Wong et al (2019) and Wong et al (2021) observed a statistically significant difference in category 1 and category 5 when FNAB with ROSE compared with FNAB without ROSE 17 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a College of American Pathologists survey, only 16.8% (82 of 488) were aware of the IAC Yokohama System 13 . Through their retrospective analysis, Sundar et al 14 concluded that the combination of the findings of the Breast Imaging‐Reporting and Data System (BI‐RADS) with the IAC Yokohama System may yield the best results for the proper stratification of breast lesions. However, substantial evidence in support of how to best use the classification systems is lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%